Enhanced Performance with the Incorporation of Organo-metal Trihalide Perovskite in Nanostructured ZnO Solar Cell. (2016) - Kumar, S.; Pradhan, S.; Dhar, A.
Abstract: The tremendous developments in the field of organic photovoltaics (efficiency>12%) in recent years has opened up a new possibility for the commercialization of low cost, flexible, and third generation photovoltaics. However, the rapid degradation of the organic materials and their short exciton diffusion lengths are major hindrance for the complete development of organic solar cells for commercial use. The concept of organic/inorganic hybrid solar cell which combines the advantages of both organic and inorganic materials are readily applicable for low cost, low temperature, high yield, and solution processable techniques but suffers from low fundamental efficiency. Recently, a new class of orgnanic/inorganic hybrid material known as organometal trihalide perovskites have emerged which exhibit the properties of good absorbtion, free charge carrier generation and efficient transport of the generated carriers while maintaining the primary requirements of organic electronics viz. low temperature and solution processability. In our present work, we have demonstrated the enhancement in device efficiency by incorporating organometal trihalide perovskite (CH3 NH3 PbI3 ) into ZnO nanostructured/MDMO-PPV inverted solar cell. The devices with perovskite absorbers showed a photocoversion efficiency of 1.97% in contrast to mere 0.06% obtained for ZnO/MDMO-PPV devices.